Race, Gender, and the Development of Cross-Race Egalitarianism - Gaither, Sarah E.; Perlin, Joshua D.; Doan, Stacey N. (Frontiers in Psychology, 2020)
Over the course of development, children acquire adult-like thinking about social categories such as race, which in turn informs their perceptions, attitudes, and behavior. However, children’s developing perceptions of race have been understudied particularly with respect to their potential influence on cross-race egalitarianism. Specifically, the acquisition of racial constancy, defined as the perception that race is a concrete and stable category, has been associated with increased awareness of racial stereotypes and group status differences. Yet, little work has investigated behavioral outcomes stemming from the acquisition of racial constancy beliefs. Here, we investigate whether the presence or absence of racial constancy beliefs differentially predicts inequality aversion with racial ingroup versus outgroup members for young children. White children (N = 202; ages 3–8) completed three sticker resource-allocation games with either a White or a Black partner shown in a photograph, after which racial constancy was measured. Results revealed that the acquisition of racial constancy interacted with partner race to predict inequality aversion outcomes in one game; however, age and gender also exerted strong effects.